Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland - Shattuck, Steve (Zootaxa, 2005)
The Camponotus aureopilus species-group is defined for the first time and revised at species level. The group contains nine known species: aureopilus Viehmeyer (with its new junior synonym, velutinus Stitz), cyrtomyrmodes Donisthorpe, densopilus new species, flavocrines Donisthorpe, mussolinii Donisthorpe, posteropilus new species, subpilus new species, thadeus new species and xanthopilus new species. All species are limited to Papua New Guinea except for thadeus, which is found in Queensland, Australia. The distinctive species C. thadeus is only the second in this large and widespread genus to possess a metapleural gland.